Program Berbasis Masyarakat dalam Upaya Pengurangan Risiko Bencana di Kabupaten Pandeglang - Anita Yunia; Janette Maria Pinariya; Diandra Forceila; Lystia Ivana (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2020)
Since 1950, the need for the global economy related to natural disasters has increased 14 fold. The natural disaster that occurred in 2018, put Indonesia into the country with the highest number of victims in the world, which was caused by three rare phenomena. This study discusses about the Desa Tangguh Bencana program as a strategic step for community-based disaster risk reduction in the Pandeglang Regency, which is one of the areas that has the impact of damage and casualties from the tsunami phenomenon in the Sunda Strait. This study aims to obtain information about the activity steps and communication strategies of the program which refers to the concept of disaster mitigation according to George D. Haddow and Kim S. Haddow in 2014. The research method uses a descriptive qualitative approach with an interpretive paradigm. Data was collected through semi-structured interviews and other supporting documents, which were analyzed using the Miles & Huberman method and tested for credibility by triangulation of sources. The results showed that community participation in this program is the main key as a planning initiator to the implementing activities. These disaster risk reduction efforts are carried out by identifying community risks, determining action plans, funding, involving opinion leaders as parties raised by the community, forming messages, to the communication channel mechanism.